2006
DOI: 10.2175/106143006x98796
|View full text |Cite
|
Sign up to set email alerts
|

Municipal Wastewater Treatment by Moving‐Bed‐Biofilm Reactor with Diatomaceous Earth as Carriers

Abstract: This study was conducted to examine the feasibility of using a moving‐bed‐biofilm reactor with internal circulation through aeration for the treatment of municipal wastewater. The attached film was a mixed‐microorganism consortium, which used composite‐refined‐diatomaceous earth as novel biomass carriers to form a diatomaceous‐earth‐moving‐bed‐biofilm‐reactor (DEMBBR) process. The startup of laboratory‐scale, continuous‐flow reactor was successfully achieved without seeding activated sludge. The DEMBBR process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 6 publications
0
10
0
4
Order By: Relevance
“…Tap water backwash, air backwash or mechanical brushing can readily clean the dynamic membrane without using any chemical reagents (Al-Malack and Anderson, 1997;Fan and Huang, 2002;Ye et al, 2006). It was reported that diatomite particles could be used as carriers for microorganisms (Zhao et al, 2006). The microbial colonies can form zoogloeas on diatomite particles through microbial capsules and surface mucus and bio-diatomite is thus named.…”
Section: Introductionmentioning
confidence: 99%
“…Tap water backwash, air backwash or mechanical brushing can readily clean the dynamic membrane without using any chemical reagents (Al-Malack and Anderson, 1997;Fan and Huang, 2002;Ye et al, 2006). It was reported that diatomite particles could be used as carriers for microorganisms (Zhao et al, 2006). The microbial colonies can form zoogloeas on diatomite particles through microbial capsules and surface mucus and bio-diatomite is thus named.…”
Section: Introductionmentioning
confidence: 99%
“…The microbial colonies on diatomite can form zoogloeas through microbial capsules and surface mucus, which are called bio-diatomite. The bio-diatomite combined with anoxic and/or aerobic processes, namely bio-diatomite reactor, has become a new wastewater treatment technology [22,23]. The bio-diatomite concentration in the reactor is usually above 10,000 mg/L.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of wastewater temperature on the rate of nitrification in a MBBR treating secondary effluent of municipal wastewater and operated under ammonialimiting and oxygen-limiting conditions were studied by supplying pure oxygen (Salvetti et al, 2006) The study on hydrodynamic behavior of a MBBR on seawater denitrifcation revealed that denitrification was optimized by modifying operating conditions (45% retention grid inclination and 30% filling ratio) and choice of carrier (Dupla et al, 2006). Diatomaceous earth was used as biofilm carrier in a MBBR to study the feasibility of its application in treating municipal wastewater (Zhao, Cao et al, 2006). With internal recirculation, and 2.5 hours of HRT, the MBBR achieved maximum of 88.5%, 83%, 92.3% and 96.7% of COD, total phosphorus (TP), NH 4 -N and turbidity of removal efficiencies, respectively.…”
Section: Moving Bed Biofilm Reactor a Review Ofmentioning
confidence: 99%